Moving On, Staying Behind, Getting Lost: Lessons on poverty mobility from longitudinal data. - Dercon, S; Shapiro, J (GPRG, 2007)
This paper gives a selected review of some of the work on poverty mobility, largely based on recent research. The literature is vast and many interesting suggestive findings have emerged. Most evidence points to the importance of household endowments, in terms of education or assets, as well as community characteristics, in terms of roads and other infrastructure, to allow movement out of poverty. For urban areas, location and access to particular types of jobs appears to matter. The paper revisits this evidence. However, in analyzing poverty mobility, it is not self-evident to move from describing the correlates of poverty mobility to understanding the causal linkages in standard data sets. A related problem involves the methods used, not least the tracking rules and the high attrition rates in most panel data surveys. We illustrate both the evidence as well as some of the problems related to the evidence using panel data from Ethiopia and Tanzania.